2008
DOI: 10.1371/journal.pone.0002942
|View full text |Cite
|
Sign up to set email alerts
|

Control of Bone Mass and Remodeling by PTH Receptor Signaling in Osteocytes

Abstract: Osteocytes, former osteoblasts buried within bone, are thought to orchestrate skeletal adaptation to mechanical stimuli. However, it remains unknown whether hormones control skeletal homeostasis through actions on osteocytes. Parathyroid hormone (PTH) stimulates bone remodeling and may cause bone loss or bone gain depending on the balance between bone resorption and formation. Herein, we demonstrate that transgenic mice expressing a constitutively active PTH receptor exclusively in osteocytes exhibit increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
353
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 344 publications
(384 citation statements)
references
References 77 publications
25
353
0
6
Order By: Relevance
“…As PTH is a known inhibitor of SOST transcription, sclerostin would not be expected to be induced if PTH was the initial driver for elevated bone formation. (72)(73)(74) Indeed, subsequent decline in sclerostin later in disease progression may be attributed to the rising levels of PTH (Figs. 1D and 8B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As PTH is a known inhibitor of SOST transcription, sclerostin would not be expected to be induced if PTH was the initial driver for elevated bone formation. (72)(73)(74) Indeed, subsequent decline in sclerostin later in disease progression may be attributed to the rising levels of PTH (Figs. 1D and 8B).…”
Section: Discussionmentioning
confidence: 99%
“…(75) In support of this, transgenic mice expressing constitutively active PTH receptors have a bone phenotype similar to osteitis fibrosa. (74) However, it is also possible that elevations in sclerostin may contribute to repression of PTH signaling in CKD bones because PTH responses are blunted in transgenic mice overexpressing sclerostin. (76) Finally, the underlying defect in jck mice is due to activating mutations in Nek8, a gene encoding a serine protease kinase that promotes protein trafficking of two cilia-associated proteins, polycystin 1 and 2 (PC1 and PC2).…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were done 60 mm away from the growth plates as described. (35,36) Serum biochemistry Blood was collected 2 and 4 weeks after pellet implantation from the facial vein of 3-hour fasted mice. N-terminal propeptide of type I procollagen (P1NP), C-terminal telopeptides of type I collagen (CTX), and tartrate-resistant acid phosphatase form 5b (TRAP 5b) were measured using enzyme-linked immunosorbent assays (Immunodiagnostic Systems Inc., Boldon, UK).…”
Section: Mice and Tissue Procurementmentioning
confidence: 99%
“…In mice, intermittent PTH was found to decrease sclerostin expression in bone by about 50%. (66)(67)(68) In the case of continuous PTH infusion (67) or osteocyte-specific constitutively elevated PTH signaling, (69) the effect was more pronounced, with sclerostin expression being decreased by more than 80%. Experiments using in vitro approaches have shown that PTH can downregulate sclerostin expression through the MEF2 transcription complex in a downstream enhancer region for the sclerostin gene.…”
Section: Osteocytes Mechanical Loading and Interface With The Pth Pmentioning
confidence: 99%